THE POLICY OF THE RUSSIAN STATE IN THE NORTH CAUCASUS IN THE PERIOD GOVERNMENT OF FIRST ROMANOV (1613-1645) - Aleksandr A. Kudryavcev; Eugene A. Kudryavcev (Вестник Северо-Кавказского федерального университета)
The article relates to by-ways of Russian history - development of relations of the Russian State with peoples of the Northern Caucasus in the first half of the XVIIth centurie.